Implementation of Tourism Promotion at The Department Culture of Luwuk Regency - Hendro Priyono, Arif; Fadli, Rachmadian (Decision, 2025)
This study aims to determine the implementation of tourism marketing and promotion policies at the Department of Tourism and Culture of West Bandung Regency. In this study using qualitative research methods with a case study approach. Data collection techniques in this study were carried out by observation, interviews and documentation. And the data analysis used is using memos, coding, transcripts and data categorization. Based on the research obtained, it can be seen that the Implementation of Tourism Marketing and Promotion Policies at the Tourism and Culture Office of West Bandung Regency aims to increase tourist visits to tourist destinations in West Bandung Regency. Tourism marketing and promotion policies have been implemented at the Tourism and Culture Office of West Bandung Regency and tourist destinations in West Bandung Regency but there are still shortcomings that cause the success of the Implementation of Tourism and Tourism Promotion Policies at the Tourism and Culture Office of West Bandung Regency.